Financial Transactions Flow Chart of Fish Marketing at Fish Landing Center (PPI) Lhok Pawoh - Asbahrul Amri; Hardianto Zainal; Meraty Ramadhini; Safrijal; Fahri Maulana; Muhammad Firdaus (Jurnal Inotera, 2020)
The fisheries and marine sector is one of the significant sectors in Aceh Province where more than 55% population of Aceh depend on this sector. Based on the results found in 2014 data collection, fisheries production by South Aceh fishermen reached 20,370.06 tons / year which was marketed inside and outside South Aceh. The problem to be examined in this study is to determine the flow chart of financial transactions in the marketing of fish at the Fish Landing Center level as part of efforts to determine the quality and safety of the catch. This research is designed to answer how the financial transaction process and payment process between market operators. The type of data used in this study is in the form of primary data and secondary data. Qualitative analysis is carried out descriptively which aims to find out deeply about financial transactions at the Lhok Pawoh Fish Landing Center. The results of this study indicate that the type of transaction used at the Fish Landing Center uses external transactions with the payment method divided into two types, namely cash payments and non-cash payments. Most of financial transaction process carried out by market operators at PPI Lhok Pawoh is using the non-cash payment method, except for muge motor which originating from outside of Lhok Pawoh Village, muge lapak and consumers who buy fish directly to PPI. In addition, It is also found that only 25% of muge motor make cash payments.